Bank Vole Prion Protein As an Apparently Universal Substrate for RT-QuIC-Based Detection and Discrimination of Prion Strains. - Christina D Orrú; Bradley R Groveman; Lynne D Raymond; Andrew G Hughson; Romolo Nonno; Wenquan Zou; Bernardino Ghetti; Pierluigi Gambetti; Byron Caughey (PLoS Pathogens)
Prions propagate as multiple strains in a wide variety of mammalian species. The detection of all such strains by a single ultrasensitive assay such as Real Time Quaking-induced Conversion (RT-QuIC) would facilitate prion disease diagnosis, surveillance and research. Previous studies have shown that bank voles, and transgenic mice expressing bank vole prion protein, are susceptible to most, if not all, types of prions. Here we show that bacterially expressed recombinant bank vole prion protein (residues 23-230) is an effective substrate for the sensitive RT-QuIC detection of all of the different prion types that we have tested so far--a total of 28 from humans, cattle, sheep, cervids and rodents, including several that have previously been undetectable by RT-QuIC or Protein Misfolding Cyclic Amplification. Furthermore, comparison of the relative abilities of different prions to seed positive RT-QuIC reactions with bank vole and not other recombinant prion proteins allowed discrimination of prion strains such as classical and atypical L-type bovine spongiform encephalopathy, classical and atypical Nor98 scrapie in sheep, and sporadic and variant Creutzfeldt-Jakob disease in humans. Comparison of protease-resistant RT-QuIC conversion products also aided strain discrimination and suggested the existence of several distinct classes of prion templates among the many strains tested.